IMPLEMENTASI PRINSIP WADIAH PADA BANK SAMPAH SYARIAH MANDIRI SUMRINGAH NGAMPELSARI KECAMATAN CANDI KABUPATEN SIDOARJO - ika karlina (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTThis study aims to provide a description of the Implementation of the â€œSumringahâ€ independent sharia Â waste bank in Ngampelsari Village, Candi District, Sidoarjo Regency. At the same time to explain that the â€œSumringahâ€ independent sharia Â waste bank is in accordance with the Wadiah Principles.This research uses qualitative research methods with data analysis using descriptive data analysis to describe the reality of the implementation of the wadiah contract in the implementation of the